2021
DOI: 10.7717/peerj.12486
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of effects or interaction between the widely used herbicide, glyphosate, and a common parasite in bumble bees

Abstract: Background Glyphosate is the world’s most used pesticide and it is used without the mitigation measures that could reduce the exposure of pollinators to it. However, studies are starting to suggest negative impacts of this pesticide on bees, an essential group of pollinators. Accordingly, whether glyphosate, alone or alongside other stressors, is detrimental to bee health is a vital question. Bees are suffering declines across the globe, and pesticides, including glyphosate, have been suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 68 publications
3
17
0
Order By: Relevance
“…Products containing glyphosate may be applied to flowering weeds 73 and contaminate their pollen and nectar 54 , thus driving bee contact and oral exposure. Glyphosate showed low lethal hazards in regulatory-ready laboratory 74 and semi-field designs when dosed as pure active substance or as MON 52276 (SL formulation containing 360 g glyphosate/L) 75 . A recent study found ready-to-use consumer products containing glyphosate to be lethally hazardous to bumble bees 73 .…”
Section: Methodsmentioning
confidence: 99%
“…Products containing glyphosate may be applied to flowering weeds 73 and contaminate their pollen and nectar 54 , thus driving bee contact and oral exposure. Glyphosate showed low lethal hazards in regulatory-ready laboratory 74 and semi-field designs when dosed as pure active substance or as MON 52276 (SL formulation containing 360 g glyphosate/L) 75 . A recent study found ready-to-use consumer products containing glyphosate to be lethally hazardous to bumble bees 73 .…”
Section: Methodsmentioning
confidence: 99%
“…The reduced mortality in the Amistar + C. bombi treatment is likely stochastic, as there is little reason C. bombi would ameliorate the impacts of the pesticide. It is worth noting that this work pre-dates the experiments in Straw and Brown (2021) [ 52 ], so the mortality was unexpected, hence the sample size for the haemoproteome analysis is reduced as only living bees had haemolymph extracted.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, (iii) glyphosate, a herbicide that is the world’s most used pesticide [ 49 , 50 ]. The impacts of glyphosate on bees are hotly contested [ 51 , 52 ], with the most rigorous evidence pointing to potential sublethal impacts on the microbiome [ 53 ], with conflicting evidence as to lethal effects [ 54 , 55 , 56 ]. To represent the most likely co-exposure situation in the field, we used the trypanosome gut parasite C. bombi , which is the most prevalent parasite of bumble bees across Europe [ 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…As our results and previous studies show (e.g., Siviter et al, 2021a ), most of these experiments have used viruses and Nosema spp. In honey bees (e.g., Doublet et al, 2014 ; Harwood and Dolezal, 2020 ; Paris et al, 2020 , 2018 ; Retschnig et al, 2015 ; Vidau et al, 2011 ), and Crithidia bombi in bumble bees ( Baron et al, 2014 , 2017 ; Fauser-Misslin et al, 2014 ; Fauser et al, 2017 ; Straw and Brown, 2021a ). While important parasites, these are only a tiny subset of the parasites and pathogens known to infect these two groups of social bees ( Schmid-Hempel, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, insecticides are not the only agrochemical group that could impact bee health. Herbicides and fungicides are heavily used around the globe, and have been shown to have negative effects on bee health (e.g., Belsky and Joshi, 2020 ), as have other ingredients within agrochemical applications (e.g., Straw and Brown, 2021a ). Given this, studies of interactions between stressors need to incorporate a more balanced approach, which recognizes the potential importance of other agrochemicals ( Straw et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%